Importance of the seryl and threonyl residues of the fifth transmembrane domain to the substrate specificity of yeast plasma membrane Na+/H+ antiporters - Kinclova-Zimmermannova, Olga; Zavrel, Martin; Sychrova, Hana (Molecular membrane biology, 2006)
The Zygosaccharomyces rouxii Na+/H+ antiporter Sod2-22p is a member of the subfamily of yeast plasma membrane Nha/Sod antiporters that do not recognize potassium as their substrate. A functional study of two ZrSod2-22p mutated versions that improved the tolerance of a S. cerevisiae alkali-metal-cation sensitive strain to high extracellular concentration of KCl identified two polar non-charged amino-acid residues in the fifth transmembrane domain, Thr141 and Ser150, as being involved in substrate recognition and transport in yeast Nha/Sod antiporters. A reciprocal substitution of amino-acid residues with a hydroxyl group at these positions, T141S or S150T, produced a broadened cation selectivity of the antiporter for K+, in addition to Na+ and Li+. Site-directed mutagenesis of Ser150 showed that while the replacement of Ser150 with a small hydrophobic (valine) or negatively charged (aspartate) amino acid did not produce a significant change in ZrSod2-22p substrate specificity, the introduction of a positive charge at this position stopped the activity of the antiporter. This data demonstrates that the amino-acid composition of the fifth transmembrane domain, mainly the presence of amino acids containing hydroxyl groups in this part of the protein, is critical for the recognition and transport of substrates and could participate in conformational movements during the binding and/or cation transport cycle in yeast plasma membrane Na+/H+ antiporters.
Keywords: Molecular Sequence Data; Saccharomyces cerevisiae; Protein Structure, Tertiary; sekvence aminokyselin; iontový transport; Na(+)-H(+) antiport; substrátová specifita; Cell Membrane; polymerázová řetězová reakce; serin; Amino Acid Substitution; Polymerase Chain Reaction; substituce aminokyselin; Mutagenesis, Site-Directed; fungální proteiny; Threonine; Serine; Ion Transport; mutageneze cílená; Protein Conformation; threonin; Fungal Proteins; Sodium-Hydrogen Exchangers; Amino Acid Sequence; Substrate Specificity; buněčná membrána; sodík; molekulární sekvence - údaje; Sodium; terciární struktura proteinů; konformace proteinů